Development of a validated HPLC method for the determination of sennoside A and B, two major constituents of Cassia obovata Coll. - Ghassemi-Dehkordi Nasrollah; Ghanadian Mustafa; Arabha Sajjad (Shahrekord University of Medical Sciences, 2014)
Introduction: Cassia obovata Coll is the only Senna species which grows wild in Iran. In the present study, an optimised reverse High Performance Liquid Chromatography (HPLC) validated method was established for quantification of sennosides A and B, the major constituents of C. obovata with a simple and accurate method. Methods: HPLC analysis was done using Waters 515 pump on a Nova-Pak C18 (3.9 × 150 mm). Millennium software was used for the determination of the sennoside A and B in Cassia species and processing the information. The method was validated according to USP 32 requirements. Results: The solvent impact on the selectivity factor and partition coefficient parameters evaluated. Using a conventional RP-18 L1 column, 3.9 × 150 mm, the mobile phase was selected after several trials with different mixtures of water and acetonitrile. Sennosides A and B were determined using the external standard calibration method. Using USP 35-NF 30, the LOD and LOQ were calculated. The reliability of the HPLC-method for analysis of sennoside A + B was validated through its linearity, reproducibility, repeatability, and recovery. Fina1ly ethanol:water (1:1) extracts of Cassia obovata and Cassia angustifolia were standardized by assay of sennoside A and B through above HPLC validated method. Conclusion: Through the above method, determination of sennosides in Cassia species are completely possible. Moreover, through comparing the results, even though sennosides are rich in Cassia angustifolia but, the results shows that C. obovata could be considered as an alternative source for sennosides A and B.